Danie letnie, lecz w zasadzie lekkostrawne - Sarnek, Marcin (Er(r)go. Teoria - Literatura - Kultura, 2002)
Marcin Sarnek's review of "Food, Drink and Identity. Cooking, Eating and Drinking in Europe since the Middle Ages," edited by Peter Scholliers(2001).